Contribution of Transposition Procedure to the Structural Adjustments in the Translation of English Memorandum of Understanding into Indonesian - Sudana, I Gede Putu; Putra Yadnya, Ida Bagus (e-Journal of Linguistics, 2021)
This current study, in which the descriptive qualitative approach is applied, is intended to reveal the extent to which the transposition procedure contributes to the structural adjustments in the translation of an English Memorandum of Understanding into Indonesian language. The data were collected through observation using close reading and note-taking techniques and qualitatively analyzed. The structural adjustments are adopted from the theories proposed by Viney and Darbelnet (in AUSSI, 1987: 143-147) and Catford (in AUSSI, 1987:145). The result of analysis shows that the Transposition Procedure highly contributes to the structural adjustments in the translation of the Memorandum of Understanding. They allow the translator to obtain dynamic equivalence and support the readability, acceptability and naturalness of the TL.